Modelling seasonal variation of sediment connectivity and its interplay with river forms - Blåfield, Linnea; Calle, Mikel; Kasvi, Elina; Alho, Petteri (Elsevier, 2025)
Functional connectivity refers to the system dynamics and sediment transfer in a geomorphological system. It is usually quantified through digital elevation models of difference at two time-steps but measuring and quantifying sediment connectivity variation between the time-steps remains a challenge. In this study we utilised a combined approach of morphodynamic model and field observation for assessing seasonal spatio-temporal variation of longitudinal functional connectivity over a 6-kilometre sub-arctic river reach. Comprehensive field datasets including sediment sampling, monitoring of morphological change and continuous discharge and water level measurements, were collected multiple times during the year to calibrate and validate the model for one year. The results revealed that connectivity inside the reach is episodical and not all the morphological adjustment was tied to discharge. Connectivity varied spatio-temporally inside the reach and sediment source and sink areas could be detected. Outside of the hydrological controlled episodes, meander evolutional stage and grain size had notable role in sediment connectivity in the short-term, and therefore underlaying morphological adjustment in the long-term. This approach can contribute to enhancing already existing connectivity indices towards a functional model considering the seasonality and periodicity of connectivity in more detail and would therefore enhance river management and prediction of geomorphic systems functioning.